Feasibility of percutaneous coronary intervention using a 7-French thin-walled sheath via the distal radial access - Ji Woong Roh; Oh-Hyun Lee; Seok-Jae Heo; Yongcheol Kim; Eui Im; Deok-Kyu Cho (Scientific Reports)
Abstract We evaluated the feasibility and safety of the 7-Fr hydrophilic coated thin-walled sheath for distal radial access (DRA) - percutaneous coronary intervention (PCI). We prospectively collected data from 100 patients who underwent PCI via DRA with a 7-Fr hydrophilic thin-walled sheath at a single center in Korea between August 2021 and April 2024. Co-primary outcomes were PCI success rate and access site complications assessed by vascular ultrasound during hospitalization and at 1-month follow up. The mean age of study population was 65.9 years, and all patients presented acute coronary syndrome. DRA-PCI was successful in all patients. Of the 43 patients evaluated forearm radial artery with intravascular imaging after PCI, there were 2 cases of thrombus and 1 intimal dissection. Access site complications included 2 small hematomas and 1 hand edema. Vascular ultrasound performed the day after PCI showed no forearm radial artery occlusion (RAO) but 2 distal RAO cases without serious complications. At 1 month follow-up, 2 consistent and 1 new case of distal RAO were observed without hand dysfunction. The SEVEN-BOX trial showed that DRA using a 7-Fr hydrophilic coated thin-walled sheath could be a feasible and safe option for complex PCI. Clinical trial registration: https://www.clinicaltrials.gov . Unique identifier: NCT05006027.